The Extended Theory of Planned Behavior to Measure Sharia Investment Intention Among the Z Generation - Fahmi, Much. Maftuhul; Suprayitno, Eko; Yuliana, Indah; Ekowati, Vivin Maharani; Rofiq, Aunur (Universitas Darussalam Gontor, 2024)
This study examines Generation Z's sharia investment preferences in light of Islamic financial literacy and religion. The Theory of Planned Behavior (TPB) was utilized to analyze attitudes, subjective norms, and Perceived Behavioral Control as mediators. This quantitative study used an explanatory technique and a representative sample of 221 students from the University of Indonesia Maulana Malik Ibrahim Malang Faculty of Economics. This study used purposive and proportional sampling. This study uses Google Forms to collect primary data and give surveys. The Likert scale (1–5) measures participants' answers. SEM-PLS analysis is used to assess 55 items across six variables in this study. The analysis uses SmartPLS 3.0. This study shows that Generation Z's interest in Islamic Capital Market is not largely driven by religion or financial knowledge in Islam. The Theory of Planned Behavior (TPB) variables may affect Generation Z's intention in sharia investing. This study shows an indirect association between Islamic Financial Literacy and Religiousness and Generation Z's intention in Sharia investments.